(3ebheGJ fXGe GdMce GdhVYj hGdESdGej (B:s (3OQGSI ebGQfI (B/s - (3YGeQ, MeOj YWjI eUWais ((3GdEScfOQjI, eUQ (B:s (3ecJHI GdhaGA GdbGfhfjI,s, 2020)
(3jJfGhd cJGH (B((3ebheGJ fXGe GdMce GdhVYj hGdESdGej (B: (3OQGSI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3MeOj YWjI eUWai YGeQ(B) (3aj MhGdj (B(559) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdMce GdhVYj(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdaUd GdChd (B: (3eGgjI GdMbhb hGdMQjGJ GdaQOjI aj GdfXGe GdhVYj hGdESdGej, GdaUd GdKGfj (B: (3efgL GdfXGe GdhVYj hGdESdGej aj GdGYJQGa HGdMbhb hGdMQjGJ GdaQOjI, GdaUd GdKGdK (B: (3GdGYJQGa HGdMbhb hGdMQjGJ GddUjbI HTNU GdEfSGf aj GdfXGe GdhVYj hGdESdGej, GdaUd GdQGHY (B: (3GdGYJQGa HGdMbhb hGdMQjGJ GdeYfhjI hGdNGUI HacQ GdEfSGf aj GdfXGe GdhVYj hGdESdGej(B.s
(3GdGYJQGa HMbhb GdEfSGf(B-(3eGgjI Mbhb GdEfSGf(B-(3efGgL GdGYJQGa HMbhb GdEfSGf(B-(3GdGYJQGa HGdMbhb GdTNUjI (B-(3GdGYJQGa HGdMbhb GdeYfhjI Ch GdNGUI HacQ GdEfSGf(B-(3GdGYJQGa HGdMbhb GdSjGSjI(B-(3GdGYJQGa HGdMbhb GdGbJUGOjI(B-(3GdGYJQGa HGdMbhb GdGLJeGYjI(B.s
Keywords: (3GdMce GdhVYj (B((3CUhd abg(B)s; (3Mbhb GdEfSGf (B((3abg ESdGej(B)s; (3Mbhb GdEfSGfs -- (3bhGfjf hJTQjYGJs; (3Mbhb GdEfSGf (B((3bGfhf Ohdj(B)s; (3Mbhb GdEfSGf (B((3bGfhf Ohdj(B)s -- (3eYGgOGJs; (3GdMbhb GdSjGSjI s -- (3bhGfjf hJTQjYGJs; (3GdMbhb GdSjGSjI (B((3abg ESdGej(B)s; (3GdMbhb GdeOfjIs -- (3bhGfjf hJTQjYGJs; (3GdMbhb GdeOfjI (B((3abg ESdGej(B)s